Phylogeny of multiple genomic regions of infectious laryngotracheitis virus in Turkish poultry flocks - O. Aydin; E. Bayraktar; HE Tali; I.E. Ozkan; A. Yilmaz; S. Umar; OE. Bamac; N. Turan; C. Konuk; Jean-Remy Sadeyen; Pengxiang Chang; JA. Richt; et al. (Poultry Science)
Infectious laryngotracheitis (ILT) is an economically significant respiratory tract viral disease affecting poultry worldwide. There is a scarcity of data on the types of ILTV strains circulating in Turkey. This study aimed to determine the frequency and genotypic variations of Turkish ILTV strains. Commercial layer flocks (n = 14) and broiler flocks (n = 105) with a history of respiratory diseases were visited. From each flock, 5 to 10 birds from different age groups were necropsied. Clinical and pathological lesions were recorded, and tracheal tissue samples were collected for further studies. Nucleic acid was extracted from samples and subjected to ILTV detection using PCR assays. Clinical signs of anorexia, lethargy, swollen eyelids, mild to severe conjunctivitis, mucoid to purulent nasal discharge, and a drop in egg production were generally observed among ILTV-infected flocks. Pathological lesions, including conjunctivitis, mucoid to purulent sinusitis, and hemorrhagic tracheitis, were observed during necropsy. Among 119 flocks (14 layers and 105 broiler) analyzed in this study, 17 (17/119, 14.28 %) flocks were found positive for ILTV infection by PCR. Of the 17 ILTV-positive samples, 15 could be sequenced successfully for partial gB, gG, and ICP4 genes. Comparative analysis of partial ICP4 gene nucleotides revealed a unique 18 bp insertion ''GCGGTTCTTGCGGTTGTT'' among ILTV strains. Two nucleotide substitutions were observed in gB gene sequences at positions 5 (T to C) and 488 (A to G), resulting in amino acid substitutions at positions 2 (I to T) and 163 (K to R). Phylogenetic analysis of the gB gene revealed a close clustering (Cluster I) between ILTV strains from this study and those reported from China, Australia, and the USA. Phylogenetic analysis of gG gene sequences showed a close relation to ILTV strains from Russia, China, Canada, the USA, and Italy. No recombination events were observed among the partial sequences of ILTV genes analyzed in this study. Findings of this study show that ILTV infections are frequent in Turkish poultry flocks and contribute to our understanding of the genomic variations in gB, gG and ICP4 genes of ILTV which might help to mitigate ILTV infections in Turkey.